HbA1c reduction following flash monitoring commencement is not independently associated with adverse diabetic eye disease outcomes in type 1 diabetes. Issue 2 (1st November 2020) - Al-Dalla Ali, Muhammad; Stimson, Roland H; Dover, Anna R; Forbes, Shareen; Annoh, Roxanne; Madill, Karen; Gibb, Fraser W
Abstract : Introduction: Intensification of therapy has been associated with early worsening of retinopathy prior to subsequent risk reduction. We sought to assess whether glycated hemoglobin (HbA1c) reduction, following flash monitoring, was associated with early worsening. Research design and methods: An observational study in 541 individuals with type 1 diabetes and paired HbA1c and eye assessment prior to and following flash monitoring commencement. Results: Change in HbA1c was −4 mmol/mol (IQR −9–1) (−0.4% (−0.8–0.1)) and 25% achieved a fall in HbA1c of ≥10 mmol/mol. The occurrence of the composite end point (panretinal photocoagulation, macular laser or anti-VEGF therapy) was associated with baseline HbA1c >75 mmol/mol (9.0%) (HR 4.0 (95% CI 2.0 to 7.9), p<0.001) but not with fall in HbA1c of ≥10 mmol/mol (0.9%) (HR 1.6 (95% CI 0.8 to 3.2), p=0.203) over a follow-up period of 615 days (527–863). In multivariate analysis, diabetes duration (p=0.035) and prior retinopathy (p<0.001) were most predictive of the composite end point. Baseline HbA1c was the strongest predictor of worsening retinopathy (p=0.002) or new retinopathy (p=0.002) in multivariate analysis whereas change in HbA1c was not independently associated with either (p=0.930 and p=0.830, respectively). Conclusions: Progression of eye disease is associated with baseline HbA1c, diabetes duration and previous retinopathy and such individuals should be monitored during intensification of glycemic therapy. Reassuringly, the extent of glucose lowering does not appear to be an independent risk factor for early worsening of eye disease in this context.